Design and Simulation Study of Excitation Coil System with Different Array Configurations for Magnetic Particle Imaging Application - Birahim, Muhamad Fikri Shahkhirin; Othman, Nurmiza; Sapuan, Syarfa' Zahirah; Md Tomari, Mohd Razali (International Journal of Integrated Engineering, 2020)
Magnetic Particle Imaging (MPI) is a tomographic imaging method has been introduced for three-dimensional (3D) imaging of human body with some potential applications such as magnetic hyperthermia and cancer imaging. It involves three important elements; tracer development using magnetic nanoparticles (MNPs), hardware realization (scanner using excitation and pickup coils), and image reconstruction optimization. Their combination will produce a high-quality image taken from any biological tissue in the human body based on the secondary magnetic field signal from the magnetized MNPs that are injected into human body. A homogeneous and adequate magnetic field strength from an excitation coil is needed to enhance the quality of the secondary signal. However, the complex surface topography of human body and physical properties of an excitation coil influence the strength and the homogeneity of the magnetic field generation at the MNPs. Therefore, this paper presents a new concept of excitation coil configuration to improve the magnetic field strength and the homogeneity to obtain better magnetization of MNPs to be detected in MPI. Two designs will be proposed with variation in physical properties and coil arrangement based on simulation study that will be carried out by using ANSYS Maxwell to generate magnetic field strength and homogeneity towards the targeted distance of 10 mm – 50 mm below the coils. The obtained magnetic field from the simulation was validated by the mathematical calculation using Biot-Savart Law equation. As a result, the new concept of excitation coil configuration proposed can be used to improve the MPI scanner system performance for various medical application.